PEREMPUAN TANGGUH: FEMINISME DALAM NOVEL HELLO KARYA TERE LIYE - Auliah, Nadillah Mirza; Ahmadi, Anas (Universitas Hamzanwadi, 2025)
The novel “Hello” by Tere Liye is one of the literary works that presents a representation of strong, brave, and independent women amidst the dominance of patriarchal culture. Women in this novel are depicted as being able to fight gender stereotypes and build self-awareness as free individuals. This study aims to describe the values ​​of feminism reflected in the character of strong women through the perspective of Simone de Beauvoir's existentialist feminist theory. This study uses a qualitative descriptive method with content analysis techniques that focus on the dialogue, actions, and narratives of the main characters in the novel “Hello”. Data were obtained through intensive reading and recording of relevant data based on the theory of existentialist feminism. The results of the study show that the character Ana as the main character represents a strong woman who refuses to be the Other as stated by Simone de Beauvoir. This is shown through Ana's brave attitude in facing social pressure, her courage to make decisions without relying on others, and her efforts to build her freedom and existence as a woman. The conclusion of this study confirms that the novel “Hello” not only presents empowered female characters, but also voices feminist values ​​that are relevant to women's struggles in modern society.